Electronic resource management : practical perspectives in a new technical services model - Elguindi, Anne C. (Chandos information professional series., 2012)
A significant shift is taking place in libraries, with the purchase of e-resources accounting for the bulk of materials spending. Electronic Resource Management makes the case that technical services workflows need to make a corresponding shift toward e-centric models and highlights the increasing variety of e-formats that are forcing new developments in the field.